Prevalence of psychiatric morbidity in orthopaedic inpatient: a hospital based cross-sectional study - Dawadi, Aswin Kumar; Adhikari, Shailendra Raj; Regmi, Anand Raj (International Journal Of Community Medicine And Public Health, 2023)
Background: Identification of a psychiatric problem should be a necessity part of treatment planning in orthopedic practice, and prompt referral for diagnosis and treatment should be made for better outcome. There have been very few studies in Nepal that has assessed the presence of psychiatric disorders in injured inpatients. The aim of the study was to find out the prevalence of psychiatric disorders in patients with injury admitted to the orthopedic ward of CMC teaching hospital. Methods: The study was carried out among 150 randomly selected patients of age group 18-60 years from the orthopedic ward suffering from any orthopedic injury. The study design is a hospital based cross sectional descriptive study. Diagnosis of psychiatric Disorders were made using ICD10 criteria. Data entry and analysis was done using the SPSS software version 21.0. Results: The prevalence of psychiatric disorder in patients with orthopedic injury was found to be 32% with depressive disorders being the most common diagnosis (12.1%) followed by anxiety disorder (8%) and somatoform disorder(6%). Psychiatric disorders were significantly associated with age, age group and gender. Psychiatric disorders were the most commonly found in those with patients with road traffic accident (52.1%) and those with lower limb injury (47.9%). Conclusions: Since, there is presence of psychopathology in orthopedic injured patients, early referral by the orthopedic surgeons to the psychiatric department is necessary for early evaluation and treatment.